Enhancing the independence and mobility for the elderly and disabled : a new approach for older users : [an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand] - Henriksen, Harry West (Massey University, 2013)
This applied design research expresses the increasing importance of mobility aids through redesigning and enhancing the abilities of an existing mobility walker; which creates both a new product and enlightened user experience that encourages elderly and disabled to remain active and independent in all aspects of life. Through personal experience and research, this project outlines how important mobility products are to the elderly and disabled communities and that existing products are out-dated and repeatedly fail to meet the growing needs and wants of these individuals. This is achieved through experience focused methods and processes designed to increase empathy and understanding of the target audience. This new mobility product promises to eliminate the requirement for multiple aids, and remove previous limitations that exist both socially and physically within the environment; thus strengthening the trust bond between the user and the product. This outcome therefore presents a practical solution to help support the market increase for personal mobility, through integrating new and feasible, electric capabilities in addition to redesigning the entire structure and appearance of the walker from scratch.
Keywords: Mobility devices; Self-help devices for people with disabilities; Wheelchairs; Design and construction